CALCULATION OF COMPOSITION AND PROPERTIES OF DISPERSED MATERIALS BASED ON BASALT COMPOSITION (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
For the development of the production of fiber concrete and concrete products based on waste, requirements are set for the efficiency and quality of construction work. In order to successfully implement these, it is necessary to achieve a reduction in total energy expenditure in materials and constructions, development of production, reduction of construction cost and labor, weight of buildings and structures, repair and their construction and operation.